Variations and Implications of Irisin, FGF-23, and N-MID Osteocalcin in Diabetic Osteoporosis Patients Undergoing Acarbose Plus Sitagliptin Therapy: A Prospective Cohort Analysis - Zhou, Lilan; Peng, Linghua (Journal of Medical Biochemistry, 2025)
Objective: The present study intends to explore the dynamic variations in Irisin, fibroblast growth factor 23 (FGF-23), and N-terminal propeptide of osteocalcin (N-MID) among diabetes mellitus osteoporosis (DOP) patients undergoing treatment with acarbose plus sitagliptin, as well as their ability to predict bone metabolic status and fracture risk. The ultimate objective is to identify potential biomarkers for optimizing DOP therapy.Methods: From January 2023 to March 2024, 124 DOP patients admitted to our hospital were administered acarbose in combination with sitagliptin. For comparison, 119 uncomplicated diabetes mellitus (DM) patients were recruited as controls. Serum levels of Irisin, FGF-23, and N-MID were tested both at baseline and post-treatment. Data on bone mineral density (BMD), bone metabolic markers, and fracture occurrences during follow-up were also collected.Results: Compared with uncomplicated DM individuals, DOP patients exhibited a rise in FGF-23 (P